PEDAGOGICAL IDEAS OF MIRZO ULUGBEK AND HIS CONTRIBUTION TO THE DEVELOPMENT OF EDUCATION - Zavqiyeva , Zamira; Ramazanova , Hamidabonu (Journal of Pedagogical and Philological Research, 2026)
This article discusses the development of upbringing, schools, and pedagogical thought in Movarounnahr during the late 14th to 16th centuries. Many of our scholars contributed significantly to education and schooling in Movarounnahr. Amir Temur can be regarded as the primary reformer of this period. With the establishment of the great centralized Timurid state, science, culture, and education began to flourish once again in Movarounnahr. During the reign of Amir Temur, craftsmen, scientists, artists, and engineers from many cities around the world were brought to Samarkand, and their rich experience and creative skills were extensively utilized in the fields of enlightenment, culture, and construction. Upbringing, schooling, culture, and science experienced significant growth.